The influence of work–family conflict on job stress among two groups of community corrections staff - Mack, Kristin Y. (Journal of crime and justice, 2019)
The negative individual and organizational impact of job stress is well documented for institutional correctional officers. One known predictor of job stress in this setting is work-family conflict. To date, however, no literature has assessed this relationship among community corrections staff. The purpose of this study was to determine if work-family conflict predicted job stress not only for probation/parole officers but also for residential (i.e., half-way house) staff members. Using data collected from an anonymous online survey of probation/parole and residential officers, we found that work-family conflict had a direct effect on job stress, but this relationship was conditioned by job position. Specifically, a significant interaction effect and models separated out by job position suggested that work-family conflict contributed to greater feelings of job stress for probation/parole officers but not for residential officers.